Stimulasi kemampuan Menulis Kata Melalui Media Visual Berupa Gambar Pada Pelajaran Bahasa Indonesia Kelas II SD Negeri 09 Kepahiang - Saragih, Desimah (Jurnal PGSD, 2020)
The lack of students’ ability to compose and to write words, became the basis and background of this Classroom Action Research. All of this happens, because the teacher never used any exciting material to teach the students and in the end the lesson became boring and lack of enthusiasm from the students. This research was conducted to stimulate the ability of students to write down the words using Visual Media in the form of Images. This Classroom Action Research was conducted in 2 cycles. This research was conducted in 2nd year of Public Primary School 09 Kepahiang, with the total of 20 students that consist of 8 male students and 12 Female Students. Data Collecting Technique that used in this research was Observation and Reflection. The collected data was analyzed using Qualitative and Quantitative analyzing technique. The result of this Classroom Action Research showed that by using Visual Media in the form of Images, the class activity became more fun and the students’ learning outcome improve dramatically. Based on the results of research, a conclusion can be drawn that the use of Visual Media in the form of Images can improve students’ word writing skills.